Etos Kerja Wanita Pedagang Acung dan KebertahananNilai-Nilai Sosial-Ritual di Kalangan Masyarakat Bali - Parmiti, Desak Putu (Universitas Pendidikan Ganesha, 2017)
Target of this research is to identify and formulate of free-merchant woman work ethos at central of tourism area in Bali and to know relation among ethos work of free-merchant woman with socio-culture conflict. This Research used approach